PENGARUH GABUNGAN DUA JENIS KAYU DAN JUMLAH LAPISAN TERHADAP SIFAT MEKANIS KAYU LAMINA - Marolop Sinaga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
An experiment of glued lamination has been conducted and their mechanical properties were tested. The pile component of glued laminated wood samples were prepared consisting of two jointed wood species with 2 (two), 3 (three) and 4 (four) layers. The dimension of glued laminated samples is 5 cm x 5 cm x 76 cm and all components were connected by glue. The mechanical properties observed are modulus of elasticity (MOE), modulus of rupture (MOR), compreesion parallel to the grain, shear parallel- to the grain (radial* and tangential) by Balwin universal testing machine with ASTM method.The results show that the mechanical properties glued laminated samples are adequate for construction purpose.